Law Enforcement in Suppressing the Spread of the Covid-19 Virus through the Implementation of Restrictions on Community Activities's Policy (PPKM) (Universitas PGRI Madiun, 2022)
The world is facing a disaster caused by the coronavirus disease 019 (COVID-19) pandemic where this virus has more or less infected more than six million people and claimed more than 370 thousand lives worldwide. The exposure to the spread is quite fast, one of which is Indonesia enacting the Policy for Enforcement of Community Activity Restrictions (PPKM) to suppress the spread of the corona virus. The problems that the author will describe are related to law enforcement efforts through PPKM policies and the legal basis related to sanctions given to the community who subscribe to health protocols. The research uses a normative method by using a statutory approach, books, journals, articles. The results of the study conclude that PPKM law enforcement can be concluded that it is still not effective, because looking at the reality there are still many non-essential and non-critical sectors that are still operating as usual, this can be seen from several factors, namely, legal factors, cultural factors, community factors, special factors imposing sanctions and the legal basis for the application of sanctions against people who do not comply with health protocols are clear in Article 93 of Law Number 6 of 2018 concerning Health Quarantine